EFFECT OF BT (CRY1AC) AND BGII (CRY1AC + CRY2AB) COTTON HYBRIDS ON CONSUMPTION-UTILIZATION INDICES OF EARIAS VITTELLA (FABRICIUS) - VADDE ANOOSHA; RAM SINGH; SUMIT SAINI (The Bioscan, 2015)
Effect of BGII, Bt and non Bt cotton hybrids on the consumption-utilization indices of Earias vittella (Fabricius 1794) at different days after sowing (70, 100, 120), were studied using six hybrids namely BIO 6488 Bt, BIO 6488 BGII, BIO 6488 non Bt, RCH 134 Bt, RCH 134 BGII and RCH 134 non Bt, on squares and bolls. Lowest CI, 0.13 and 0.14 was recorded on BIO6488 BGII on 70 and 100 DAS respectively. GR ranged from 0.11 to 0.20 mg/day on squares and 0.28 to 0.39 mg/day on bolls of Bt (Bt & BGII) while lowest ECI, 11.93% at 70 DAS on squares of RCH134BGII. AD/AE remain highest on non Bt (64.46-63.53%) and ranged from 30.42% (RCH134BGII) to 33.42% (BIO6488BGII) on bolls of Bt. All the parameters effected adversely from 70 to 120 DAS which may be a mixed effect of aging and decreased toxin expression. Values of ECD, 18.60 % at 70 DAS and 19.78% at 120DAS on BIO6488BGII is in accordance with above.